Accelerated ecotoxicity of photoreactive nanoparticles on - Sun-Hwa Nam; Yu-Jin Shin; Youn-Joo An (Environmental Health and Toxicology, 2017)
Zinc oxide nanoparticles (ZnO NPs) and titanium dioxide nanoparticles (TiO2 NPs) are well known as photoreactive nanoparticles (NPs). Various phototoxicities of ZnO NPs and TiO2 NPs were reported on several organisms. It was still necessary to evaluate the toxicity of photoreactive ZnO NPs and TiO2 NPs due to species-specific effects under various irradiation conditions. We compared the acute toxicity of Moina macrocopa under visible, ultraviolet (UV) A, and B irradiations, according to the Organization for Economic Cooperation and Development guidelines for the testing of chemicals (Test No. 202). The sensitivity of ZnO NPs for M. macrocopa was UVB>UVA>visible light irradiation. There were no significant lethal and immobile effects of TiO2 NPs on juveniles under all irradiations and in the tested concentrations of TiO2 NPs. Photoreactive NPs have a potential and accelerated toxicity on organisms in the ambient environments.